2014
DOI: 10.1007/s11116-014-9557-y
|View full text |Cite
|
Sign up to set email alerts
|

What makes travel pleasant and/or tiring? An investigation based on the French National Travel Survey

Abstract: The 2007-08 French National Travel Survey (FNTS) included questions about the trip experience for a random subsample of the respondents' daily travel, offering a rare opportunity to examine a national profile of attitudes toward travel. This study analyzes the self-reported (mental and/or physical) fatigue associated with the selected trip, and its (un)pleasantness. Only 8% of trips were tiring, and fewer than 4% were unpleasant, indicating that travel is by no means universally distasteful. We present a bivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 38 publications
5
104
0
7
Order By: Relevance
“…The largest category of evidence covers the activities individuals engage in while travelling and whether they consider their travel time to be useful, pleasant or wasted (Berliner Kenyon and Lyons 2007;Lyons et al 2007Lyons et al , 2013Lyons et al , 2016Russell et al 2011;Tang et al 2018;Van de Waerden et al 2009;Yosritzal et al 2017). There have also been many studies that investigate how worthwhile activities while travelling affect attitudes and journey satisfaction (Ettema et al 2012;Frei et al 2015;Mokhtarian et al 2015;Rasouli and Timmermans 2014;van Hagen et al 2017) and others that explore mode choice effects (Van der Waerden et al 2010;Etezady et al 2019;Malokin et al 2017Malokin et al , 2019. Whilst such studies tend to recognise that multitasking would be expected to reduce the VTTS, they do not seek to estimate how the worthwhile use of travel time impacts on VTTS.…”
Section: Behavioural Studiesmentioning
confidence: 99%
“…The largest category of evidence covers the activities individuals engage in while travelling and whether they consider their travel time to be useful, pleasant or wasted (Berliner Kenyon and Lyons 2007;Lyons et al 2007Lyons et al , 2013Lyons et al , 2016Russell et al 2011;Tang et al 2018;Van de Waerden et al 2009;Yosritzal et al 2017). There have also been many studies that investigate how worthwhile activities while travelling affect attitudes and journey satisfaction (Ettema et al 2012;Frei et al 2015;Mokhtarian et al 2015;Rasouli and Timmermans 2014;van Hagen et al 2017) and others that explore mode choice effects (Van der Waerden et al 2010;Etezady et al 2019;Malokin et al 2017Malokin et al , 2019. Whilst such studies tend to recognise that multitasking would be expected to reduce the VTTS, they do not seek to estimate how the worthwhile use of travel time impacts on VTTS.…”
Section: Behavioural Studiesmentioning
confidence: 99%
“…Travel time perception varies as a result of the activities carried out while traveling or waiting. Mokhtarian et al (2015) found that listening to music/radio diminishes mental fatigue and increases trip pleasantness. In addition, they indicated that talking to others increases the probabilities of perceiving a trip as pleasant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was the case more so in relation to active time uses as opposed to passive time uses (such as listening to music). For the latter, the authors suggest that use of mobile technologies is to alleviate boredom or privatise the public space (see also Mokhtarian et al (2015) regarding ameliorating a negative journey experience through listening to radio/music). Schwieterman et al (2013) highlight substantial increases in mobile technology use on passenger transport in the US: up 25% for commuter trains and 18% in intercity trains over the period 2012.…”
Section: 1mentioning
confidence: 99%